Interview with Karin Knorr Cetina: "One Implication of Our Argument is That It Accounts for the Emergence of a Parallel World, in Which Other Criteria are Relevant and Where Different Norms Count" (translated by Dmitry Krylov, Gleb Kozyritsky) - Knorr CetinaKarin (Journal of Economic Sociology, 2011)
Detailed description in the text